2016
DOI: 10.1007/s10569-016-9722-z
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Kepler and anisotropic two fixed centres problems

Abstract: In this paper we show that the anisotropic Kepler problem is dynamically equivalent to a system of two point masses which move in perpendicular lines (or planes) and interact according to Newton's law of universal gravitation. Moreover, we prove that generalised version of anisotropic Kepler problem as well as anisotropic two centres problem are non-integrable. This was achieved thanks to investigation of differential Galois groups of variational equations along certain particular solutions. Properties of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This approach is based on the analysis of the differential Galois group of variational equations of a considered system along a certain particular solution. The Morales-Ramis theory has been used recently for study integrability of various important physical and astronomical systems, see, e.g., papers [23][24][25][26][27][28][29][30][31][32][33]. We also mention review paper [34], in which certain examples can be found.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is based on the analysis of the differential Galois group of variational equations of a considered system along a certain particular solution. The Morales-Ramis theory has been used recently for study integrability of various important physical and astronomical systems, see, e.g., papers [23][24][25][26][27][28][29][30][31][32][33]. We also mention review paper [34], in which certain examples can be found.…”
Section: Introductionmentioning
confidence: 99%